Scoop, last of the brown pelicans - McClung, Robert M.; Sandford, Lloyd (New York, Morrow, 1972)
Portrays the life cycle of the brown pelican, a bird in danger of extinction.
Keywords: Brown pelican -- Juvenile literature; Brown pelicans; Pelicans